The importance of commitment, communication, culture and learning for the implementation of the Zero Accident Vision in 27 companies in Europe. (July 2017) - Zwetsloot, Gerard I.J.M.; Kines, Pete; Ruotsala, Riikka; Drupsteen, Linda; Merivirta, Maija-Leena; Bezemer, Robert A.
Graphical abstract: Highlights: Zero Accident Vision (ZAV) is based on the assumption: all accidents are preventable. ZAV initiatives focus on safety commitment, communication, culture and learning. ZAV is the basis for inspiring and innovative approaches to improve safety. ZAV is driven by organisational and individual commitment. ZAV commitment is embedded in a company's business strategy. Abstract: In this paper the findings are presented of a multinational study involving 27 companies that have adopted a 'Zero Accident Vision' (ZAV). ZAV is the ambition that all accidents are preventable, and this paper focuses on how companies implement ZAV through ZAV commitment, safety communication, safety culture and safety learning. Managers and workers took part in a survey (8, 819 respondents), company interviews and national workshops in seven European countries. A common characteristic of all the companies was the high ZAV commitment of their managers and workers, which often were embedded in the companies' business strategies. It is very likely that this commitment is the main driver for long-term safety improvements. This research supports the importance of safety communication for ZAV implementation, especially of: specific ZAV or safety promotion programmes, constant and updated communication on functional tools, and effective supervisor communication. Successful communication must ensure 'relevant' information to respective organisational levels (not a one-size fits-all strategy), and allow for 'decentralised' initiatives. This research also highlights the importance of safety culture for ZAV implementation, with ZAV companies having high survey scores on management safety priority, safety empowerment and safety justice. The results also support the importance of safety learning (incidents and good-practice) for ZAV implementation. Additional success factors were top management support and an 'open atmosphere', systematic communication and dialogue on incidents, and a focus on things that go right. We conclude that ZAV is the basis for inspiring and innovative approaches to improve safety, as an integrated part of doing business.